Work and Politics: Elements for the Reconstruction of Hannah Arendt´s Criticicism of Marx - Lucena Góngora, Borja (Res Publica. Revista de Historia de las Ideas Políticas, 2019)
This article tries to appreciate the meaning of Hannah Arendt´s critique of Marx, focusing on the way Marxian philosophy incardinates in the auto-comprehension of the modern capitalist society. In particular, it examines the new concept of human being as animal laborans, the Marxian formulation of a new conception of work suitable for the insertion men in the newly created structures of production, and the philosophical-political framework of the notion of “alienation” (Entfremdung, Entäusserung). Finally, a critical assessment of the Arendtian contribution to the understanding of the German philosopher is proposed.
Keywords: Hannah Arendt; Marx; Alienation; animal laborans, Work.